Women from Venus, men from Mars: Inter-sex foraging differences in the imperial cormorant Phalacrocorax atriceps a colonial seabird - Quintana, Flavio Roberto; Wilson, Rory P.; Dell'arciprete, Olga Patricia; Shepard, Emily; Gómez Laich, Agustina Marta (Oikos)
Colonial seabirds are central place foragers and likely to be subject to substantial competition for resources. Mechanisms proposed for reducing intra-specific competition include differential inter-sex area use mediated by adult choice. We used GPS loggers and dive recorders to study area use and dive depth in a total of 27 male and 26 female imperial cormorants Phalacrocorax atriceps breeding at a colony of some 6500 birds at Punta Leon, Chubut, Argentina during 2004 and 2005. Although time spent travelling and distances between the colony and foraging sites were similar for both sexes, males and females travelled away from their colony using routes virtually perpendicular to each other so that their foraging areas were distinctly different; females hunted close to the coast while males foraged offshore in deeper water. Consideration of foraging efficiency underwater, defined as the duration spent on the bottom divided by the dive cycle duration, showed that females were more efficient at depths < 40 m while males more efficient at depths > 40 m. We suggest that the substantial sexual dimorphism in this species may be responsible for the different depth-linked foraging efficiencies and that selection for appropriate depths could lead to differential habitat use and putative differences in prey selection. Fil: Quintana, Flavio Roberto. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico; Argentina. Wildlife Conservation Society; Estados Unidos Fil: Wilson, Rory P. Swansea University; Reino Unido Fil: Dell'arciprete, Olga Patricia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico; Argentina Fil: Shepard, Emily. Swansea University; Reino Unido Fil: Gómez Laich, Agustina Marta. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico; Argentina